Targeting potential drivers of COVID-19: Neutrophil extracellular traps - Barnes, Betsy J.; Adrover, Jose M.; Baxter-Stoltzfus, Amelia; Borczuk, Alain; Cools-Lartigue, Jonathan; Crawford, James M.; Daßler-Plenker, Juliane; Guerci, Philippe; Huynh, Caroline; Knight, Jason S.; Loda, Massimo; Looney, Mark R.; et al. (The Journal of experimental medicine, 2020)
Coronavirus disease 2019 (COVID-19) is a novel, viral-induced respiratory disease that in ∼10–15% of patients progresses to acute respiratory distress syndrome (ARDS) triggered by a cytokine storm. In this Perspective, autopsy results and literature are presented supporting the hypothesis that a little known yet powerful function of neutrophils—the ability to form neutrophil extracellular traps (NETs)—may contribute to organ damage and mortality in COVID-19. We show lung infiltration of neutrophils in an autopsy specimen from a patient who succumbed to COVID-19. We discuss prior reports linking aberrant NET formation to pulmonary diseases, thrombosis, mucous secretions in the airways, and cytokine production. If our hypothesis is correct, targeting NETs directly and/or indirectly with existing drugs may reduce the clinical severity of COVID-19.